2007
DOI: 10.1186/1471-2458-7-157
|View full text |Cite
|
Sign up to set email alerts
|

Influenza pandemic preparedness: motivation for protection among small and medium businesses in Australia

Abstract: BackgroundCommunity-wide preparedness for pandemic influenza is an issue that has featured prominently in the recent news media, and is currently a priority for health authorities in many countries. The small and medium business sector is a major provider of private sector employment in Australia, yet we have little information about the preparedness of this sector for pandemic influenza. This study aimed to investigate the association between individual perceptions and preparedness for pandemic influenza amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…Further, increasing severity consistently leads to greater intentions to behave in a health-protective manner (Rogers and Mewborn, 1976;Rogers, 1997) and fear appeals have been shown to motivate or persuade humans to protect animals as well (Shelton, 1981). Similarly, severity was an important predictive factor for influenza preparedness in a study among Australian businesses (Watkins, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Further, increasing severity consistently leads to greater intentions to behave in a health-protective manner (Rogers and Mewborn, 1976;Rogers, 1997) and fear appeals have been shown to motivate or persuade humans to protect animals as well (Shelton, 1981). Similarly, severity was an important predictive factor for influenza preparedness in a study among Australian businesses (Watkins, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…This concern may relate to the potential for loss of income or job if they comply with government recommendations, such as home isolation or quarantine, as shown by Blendon et al 27 Our findings and those of other studies suggest that educational interventions are required to improve trust in the community and to promote effective coping mechanisms that could support implementation of government strategies. 28,29 As a component of a pandemic influenza education campaign, the community must be made aware that the routine influenza vaccine will not provide protection against a novel strain and that an effective vaccine will need to be developed. 30,31 In addition, the community will need to be aware that because of delays in the provision of a vaccine, other preventive measures will be required to minimize the spread of infection, many of which could be promoted for use during seasonal outbreaks.…”
Section: Knowledge Of Pandemic Influenza Preparednessmentioning
confidence: 99%
“…This is consistent with previous findings that small and mediumsized companies are the least likely to be prepared, and, unfortunately, they are also likely to be the hardest hit during a pandemic. 28,29 It has been reported that approximately two-thirds of biotechnology companies have fewer than 50 employees. 22 This study had a higher percentage of small companies (80%), possibly because the selected region is one of the hotbed clusters in the biotechnology industry and more likely to foster new companies.…”
Section: Discussionmentioning
confidence: 99%